The Glutamate Receptors - Gereau, Robert W.; Swanson, Geoffrey (The Receptors,, 2008)
Glutamate receptors are critically important for normal brain function. The preceding decade has seen remarkable advances in our understanding of the physiological function and molecular structure of these proteins. The Glutamate Receptors provides an expansive review of the field with a topical update to two excellent books - The Ionotropic Glutamate Receptors and The Metabotropic Glutamate Receptors. An exciting primer to the study of glutamate receptors and their central role in neurotransmission, The Glutamate Receptors covers the extraordinary research and significant developments in the decade since the previous books were published and gives a snapshot of how prominent scientists look to the future of research in the field. Both insightful and comprehensive, The Glutamate Receptors provides an invaluable reference to students and scientists on nearly every aspect of glutamate receptor structure and function.